Evaluate the effect of oat-beta glucan in controlling blood glucose levels among type 2 diabetic individuals - Albalawi, Ahmad Abdulualrazag Ali; Albalawi, Fatmah Abdulrazzaq Ali (International Journal of Research in Medical Sciences, 2016)
Diabetes mellitus (DM) is a metabolic disorder characterized by inappropriate hyperglycemia due to deficiency in producing insulin or inefficient action of this hormone. Patients with DM are frequently afflicted with ischemic vascular disease, wound healing defect, vascular alterations, myocardic infarction, nephropathies, retinopathies and neuropathies. The uses of hypoglycemic agents or insulin are the common conventional treatments of diabetes. However, the frequent use of such expensive medications increased the financial burden upon patients. Low glycaemic food consumption is a very fruitful alternative in controlling diabetes. Foods that are rich in fiber are on the top of the glycaemic index and the potential component is beta glucan. The evidence of consuming oat beta-glucan to enhance glycaemia and insulin levels is not well established. So, the objective of this overview review is to evaluate the effect of oat-beta glucan in controlling blood glucose levels among type 2 diabetic individuals.